CLINICAL CHARACTERISTICS OF LOWER LIMB WOUNDS IN INJURED PEOPLE IN THE RESULT OF MODERN MILITARY OPERATIONS - Guriev, S.O.; Tanasienko, P.V.; Panasenko, S.I.; Martsynkovskyi, I.P.; Fil, A.Yu. (World of Medicine and Biology, 2020)
Studying the experience of providing surgical service to the injured people with a mine blast injures in a local armed conflict in the East of Ukraine will allow not only to determine the nature of modern war trauma, but also to make some changes in the formed ideas about the effectiveness of certain measures. The stage of professional medical services was the main one for the injured people with the neuromuscular bundle and the knee joint injuries, which was found in 5.9% and 9.5% respectively and in subsequent stages their number decreased. At the stage of specialized medical services the injured people with lower leg injuries were concentrated. 41.0% were detected at this stage, which is 1.3 times more than at the stage of professional services and almost twice more than at the stage of highly specialized medical services. The stage of highly specialized medical care was the main one for the injured people with injuries of pelvic (4.8%), buttock (7.8%), hips (34.9%), foot (16.5%) traumatic amputation of the lower leg (1.9%) and foot (3.8%).
Keywords: injured people; gunshot wounds; limbs; mine blast injury